BENTUK-BENTUK SIMBOLIK DALAM PUISI ‘PERJALANAN MALAM’ KARYA EKA BUDIANTA (TELAAH MAKNA) - Alex Djawa; Betharia Pane (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
Symbolism is part of a sign. Semiotics is the study of signs. Signs are divided into several parts, including icons, indices, signals, symptoms, and symbols. In this article, the discussion focuses solely on the symbols found and used in the poem mentioned above. It is known that symbolic forms use language in a unique sense and are not easily understood in the context of their use. Therefore, the goal is to express symbolic meanings accurately, sharply, and profoundly.